الحاجات الارشادية لدى تلاميذ الرابعة متوسط -دراسة ميدانية بمتوسطة الزهراء بولاية الاغواط- - ديدي فاطمة حنان; النية لمياء; محمد الامين عياط (My University, 2022)
The current study aimed to identify the counseling needs of the fourthintermediate students, and the descriptive analytical approach was relied on because it was the most appropriate for these topics on a sample of 60 male and female students in the middle school of Al-Zahra. The treatment of the results of this study was based on the statistical programmer for the social sciences (SPSS) system, which yielded the following results: -Arrangement of counseling needs as follows: (family needs, health needs, physical needs, social needs, psychological needs, and study needs) -There are statistically significant differences between females and males in the level of counseling needs